Innovative green building forms for sustainable community - Puah, Lesle Wei Jian. (2011)
The most vital factor contributing to urban heat island effect is the diminishing of greenery area and increased in concrete area which results in serious temperature difference between urban and rural area. The problems associated at present are that there has not been any agreement on the quantification of the impacts of wind speed on urban heating. In this project, investigation was conducted to determine the effect of wind speed and building geometry on thermal dissipation. The results will help to determine whether the proposed green building forms will mitigate the urban heat island effect. Wind speed was found to have possible effect on thermal dissipation. When wind speed increased from 1 to 5m/s, the mean temperature decreases from 23.85oC to 20.84oC and normalised air temperature deceased by 0.151. Besides wind speed, building aspect ratio was found to have a negative effect on thermal dissipation. When aspect ratio increases from 1 to 5, the mean temperature increased by 4.1oC.